As indicações geográficas como um mecanismo a resguardar o patrimônio cultural imaterial: um olhar à luz da experiência da região do Vale dos Vinhedos - Hundertmarch, Bruna (2016)
Brazil has a vast ecological wealth, a situation that favors the emergence of diverse cultures, since there are different forms of man's interaction with nature. This natural and cultural richness, named sociobiodiversity lacks legal means able to safeguard it, given the risk of extinction. For this reason, the Federal Constitution, in providing protection to an ecologically balanced environment, made it considering the environmental and cultural dimension, considering the material and immaterial dimensions. Thus, ruled not only the fauna and flora, but also cultural events and traditions, forms of expression, the celebrations, the knowledge, the means to do, among others. Therefore, when considering the contemporary society, marked by the effects of globalization, in which the global and the local sometimes get confused, a reality that is resulting in cultural pasteurization, it is important to reflect on guardianship mechanisms of immaterial cultural heritage, in view of their risk of annihilation. In this context, it deserves attention the institute of the Geographical Indications, part of the legal diploma of intellectual property, governed by Law 9.279 / 96, which was established to promote local development, adding value to products and services from regions that became known as extraction centers, of manufacturing and production of goods and services. In this study, we intend to investigate the extent to which the institute in question lends itself to promote the immaterial cultural heritage. To achieve this goal, it will be used the deductive method of approach and historical and monographic procedure methods. The basic theory to be adopted will be Capra‟s systemic theory. In conclusion, it was obtained that such institute is not limited to promoting economic growth in a given region, but is a mechanism that lends itself to promote and rescue the local culture. Furthermore, geographical indications can be taken by the side of heritage listing, the registry and the inventory, as being able to guard the immaterial cultural heritage.